Load sharing and structural response of roof–wall system in a timber-framed house. (1st September 2016) - Satheeskumar, N.; Henderson, D.J.; Ginger, J.D.; Humphreys, M.T.; Wang, C.H.
Highlights: Structural response and load sharing of contemporary Australian timber-framed house. Contribution of the structural and lining elements to the load sharing. Results show the percentage of load reduction provide by the structural and lining elements. Abstract: Full-scale tests were carried out on a part of representative brick veneer contemporary house to assess the loading effects on roof to wall connections and load sharing. Tests were carried out at each stage of construction: bare frame followed by the installation of roof battens and cladding, wall lining, ceiling, etc. These construction stages were used to assess the contribution of the structural and lining (i.e. ceiling, ceiling cornice and wall lining) elements to the load sharing and response of the timber-framed house structure to wind loading. Results of the full-scale test show that the vertical reaction force at the loaded truss support was reduced by about 20% when the lining elements were added to the system with structural elements (i.e. truss, batten and roof cladding). The vertical load sharing of the timber-framed house through the roof to wall connection (RWC) depends on the stiffness of the RWC and the truss location (i.e. whether located at the end or middle). The contribution of the lining elements to the vertical load sharing is about 15–20%. The lateral load resistance of RWCs significantly increased, when ceiling, ceiling cornice and wall lining were added to the structural system. The outcome of this study can be used to assess the structural response and vulnerability of these houses to windstorms.